Slurry composition as well as preparation method and application thereof

By using polyvinyl acetal resin B in the slurry composition, epoxy cellulose is grafted on the side chain of the molecular chain, the problems of poor dispersion and settlement stability of the slurry composition are solved, and the surface flatness and mechanical strength of the ceramic green sheet are achieved, and capacitance is improved.

CN119570267APending Publication Date: 2025-03-07ANHUI WANWEI ADVANCED FUNCTIONAL MEMBRANE MATERIALS RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811493.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The dispersion between the components of the slurry composition is poor and the settlement stability is poor, resulting in uneven concave and convexity of the ceramic green sheet surface, uneven thickness, easy cracking, and affecting capacitance.

Method used

Polyvinyl acetal resin B is used, and epoxy cellulose is grafted on the side chain of its molecular chain to form a cross-linked network structure, improving the fluidity and dispersion of the slurry, and enhancing the adhesion to the inorganic powder through the polar hydroxyl group of the epoxy cellulose, improving the anti-settlement performance.

Benefits of technology

The dispersion and settlement stability of the slurry composition are significantly improved, the surface flatness and mechanical strength of the ceramic green sheet are improved, cracking is reduced, and capacitance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180654040000031
    Figure BDA0005180654040000031
  • Figure BDA0005180654040000032
    Figure BDA0005180654040000032
  • Figure BDA0005180654040000091
    Figure BDA0005180654040000091
Patent Text Reader

Abstract

The invention discloses a slurry composition and a preparation method and application thereof, and belongs to the technical field of slurry compositions.The slurry composition is prepared from, by mass, 100 parts of inorganic powder, 1-20 parts of polyvinyl acetal resin composition, 3-5 parts of plasticizer and 50-70 parts of organic solvent; wherein the polyvinyl acetal resin composition comprises polyvinyl acetal resin A and polyvinyl acetal resin B; the side chain of a molecular chain of the polyvinyl acetal resin B is grafted with epoxy cellulose, so that the polyvinyl acetal resin can be endowed with certain thixotropy, the flowing property and the dispersity of the slurry composition are improved, and a cross-linked network structure can be formed between the modified polyvinyl acetal resin, so that inorganic powder is better wrapped, and the slurry composition is more stable in performance. And the anti-settling purpose is achieved. The polymerization degree of the polyvinyl acetal resin A is relatively low, so that the viscosity of the slurry composition can be better regulated and controlled, and the processability and the mechanical property of the slurry composition are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of slurry compositions, and in particular relates to a slurry composition and a preparation method and application thereof. Background Art

[0002] The slurry composition is a liquid-solid mixture, usually composed of water, a binder and various additives. The main characteristics of the slurry are its fluidity and plasticity. Especially in the preparation process of electronic ceramics, the properties of the slurry composition can be utilized to prepare electronic ceramics by a tape casting method.

[0003] Among them, polyvinyl alcohol acetal resin is a thermoplastic resin product with good film-forming property, impact resistance, cold resistance and radiation resistance, and has excellent adhesion to metal, glass, wood, ceramics and fiber products. Adding it as an adhesive to the slurry composition can meet general process requirements. However, the slurry composition produced will have uneven dispersion, powder agglomeration and other phenomena, and the slurry composition has poor sedimentation stability and poor rheological properties, which will further limit the application of the slurry composition. For example, in the preparation of electronic ceramics, these problems will cause the surface of the obtained ceramic green sheet to be uneven, uneven in thickness, and there will be problems such as cracking and pinholes. The strength and softness of the ceramic green sheet will also decrease accordingly. The ceramic green sheet is also prone to breakage during processing, affecting the capacitance of the finished product.

[0004] In order to improve this problem, a thixotropic agent is usually added to the slurry to improve the dispersibility, uniformity and stability of the slurry composition. However, the compatibility between the thixotropic agent and the slurry components is generally poor, resulting in a decrease in the mechanical properties of the finished product. Others have tried to improve the adhesive polyvinyl acetal resin, but the improved process parameters are difficult to control, the process is complex, the requirements for production equipment are high, and the surface of the coating is uneven. Summary of the invention

[0005] The object of the present invention is to provide a slurry composition and a preparation method and application thereof, so as to solve the problems of poor dispersibility and poor sedimentation stability between components of the slurry composition. The obtained slurry composition has a simple preparation process and a high yield.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a slurry composition, comprising the following raw materials in parts by weight:

[0008] 100 parts of inorganic powder;

[0009] 1 to 20 parts of a polyvinyl acetal resin composition;

[0010] 3-5 parts of plasticizer;

[0011] 50-70 parts of organic solvent;

[0012] The polyvinyl acetal resin composition comprises polyvinyl acetal resin A and polyvinyl acetal resin B; the molecular chain side chain of polyvinyl acetal resin B is grafted with epoxy cellulose.

[0013] Preferably, the inorganic powder includes one of barium titanate, ferrite, aluminum oxide, silicon nitride, zirconium oxide and graphene.

[0014] Preferably, the plasticizer includes a combination of one or more of triethylene glycol diisooctanoate, tetraethylene glycol diheptanoate and dipropylene glycol methyl dibenzoate.

[0015] Preferably, the organic solvent includes one or more combinations of toluene, ethanol, n-butanol, isopropanol, acetone, diethyl ether, xylene, benzyl alcohol, ethylene glycol dimethyl ether, N,N-dimethylformamide and N,N-dimethylacetamide.

[0016] Cellulose has a certain thixotropy. Its intermolecular hydrogen bonds and van der Waals forces are destroyed under the action of shear force, and the viscosity will decrease. After the shear force stops, these interactions will be re-established and the viscosity will increase. In theory, adding thixotropic cellulose to the slurry composition can significantly improve the rheological properties of the slurry. It will show a lower viscosity when subjected to shear force, which is convenient for flow and construction; while it will show a higher viscosity under static or low shear force, preventing the slurry from flowing, settling and wet film sagging. These characteristics are conducive to obtaining a slurry composition with good dispersibility and good sedimentation stability. However, since cellulose itself has a large number of polar functional groups and there is a large polarity difference between it and the non-polar inorganic powder, the interfacial adhesion between cellulose and the inorganic powder will be poor, thereby affecting the binding performance of the two, which is not conducive to the dispersion and binding between the components of the slurry composition.

[0017] By adopting the above technical scheme, the present invention provides a polyvinyl acetal resin B, on which epoxy cellulose is grafted on the side chain of the molecular chain, and the polyvinyl acetal resin has good compatibility and interface bonding force with the inorganic powder, and a good adhesion effect can be formed between the two; after grafting, the polyvinyl acetal resin also has a certain thixotropy, which can improve the dispersibility and sedimentation stability of the slurry composition. More importantly, epoxy cellulose contains a large number of polar hydroxyl groups, and after the polyvinyl acetal resin B is grafted and modified, the molecular chains can form a cross-linked network structure through intermolecular interactions, which can further wrap the inorganic powder to achieve the purpose of anti-sedimentation.

[0018] In the present invention, a variety of different inorganic powders can be used to prepare the slurry composition to meet the application requirements of different fields, simplify the process steps, and increase the application range of the slurry composition.

[0019] Preferably, the epoxy cellulose contains one or two or more epoxy groups; the molecular structure of the epoxy group is as follows:

[0020]

[0021] R1 is a C1-C15 alkyl chain; R includes one of -H and -CH3.

[0022] Preferably, epoxy cellulose comprises the following structural units:

[0023]

[0024] Wherein X, Y, and Z are any one of -H, -CH3, and epoxy groups, and the structural unit contains at least one or more epoxy groups.

[0025] Preferably, epoxy cellulose is prepared according to the following method:

[0026] The cellulose is added to a sodium hydroxide aqueous solution, stirred and mixed at room temperature for 3 to 4 hours, and then dried to obtain pretreated cellulose; the pretreated cellulose, epoxy compound and sodium hydroxide are mixed, stirred and mixed for 30 to 40 minutes in a nitrogen atmosphere, a catalyst is added, the temperature is increased to 60 to 70° C., the reaction is stirred for 5 to 6 hours, and finally epoxy cellulose is obtained by filtering, washing, suction filtering and drying.

[0027] More preferably, the mass ratio of cellulose to epoxy compound is 1:(15-20).

[0028] More preferably, the epoxy compound comprises a combination of one or more of epoxyalkyl chloride or epoxyalkyl bromide; wherein the carbon number of the linear alkyl group in the epoxyalkyl chloride and the epoxyalkyl bromide is 1-20.

[0029] More preferably, the catalyst comprises a combination of one or more of tetramethylammonium bromide, benzyltriethylammonium bromide, tetramethylammonium hydrogen sulfate, tetradecylpyridinium chloride and tetrapropylammonium iodide; and the added amount of the catalyst is 4-6% of the mass of the cellulose.

[0030] By adopting the above technical solution, the epoxy cellulose grafted with the polyvinyl acetal resin B of the present invention also has an alkyl chain introduced thereon. On the one hand, after epoxidation, the cellulose has active sites that can react and connect with the polyvinyl acetal resin.

[0031] On the other hand, the introduction of alkyl chains will increase the branch length and molecular weight of the polyvinyl acetal resin, and its flexible carbon chain can help the polyvinyl acetal resin B to cross-link with each other during the preparation of the slurry composition to form a network structure, thereby improving the mechanical strength of the slurry composition and the coating effect on the inorganic powder, thereby increasing the anti-sedimentation performance of the slurry composition. However, when the length of the alkyl chain is too long, it will produce a relatively large steric effect, affect the grafting rate of epoxy cellulose, and also cause the viscosity of the polyvinyl acetal resin to increase, thereby reducing the dispersibility of the obtained slurry composition.

[0032] Preferably, the polyvinyl acetal resin B is prepared according to the following method:

[0033] Add polyvinyl alcohol to water, stir and dissolve at 90-95° C. to obtain a polyvinyl alcohol aqueous solution; reduce the temperature of the polyvinyl alcohol aqueous solution to 30-35° C., add part of n-butyraldehyde and an acid catalyst, stir and mix for 30-60 minutes, continue to reduce the temperature to 5-10° C., add the remaining n-butyraldehyde, add epoxy cellulose after phase change and precipitation are complete, keep warm for 20-30 minutes, then raise the temperature to 40-50° C., stir and react for 2-3 hours, and finally obtain polyvinyl alcohol acetal resin B through neutralization, centrifugation and drying.

[0034] Preferably, the added amount of epoxy cellulose is 0.1-5% of the total mass of polyvinyl alcohol and n-butyraldehyde.

[0035] More preferably, the added amount of epoxy cellulose is 0.1-2% of the total mass of polyvinyl alcohol and n-butyraldehyde.

[0036] Preferably, the mass ratio of polyvinyl alcohol to n-butyraldehyde is 1:(0.5-0.65).

[0037] Preferably, the acid catalyst comprises one of hydrochloric acid, sulfuric acid, nitric acid and p-toluenesulfonic acid; the amount of the acid catalyst added is 9-10% of the total mass of the polyvinyl alcohol and n-butyraldehyde.

[0038] By adopting the above technical scheme, during the polymerization process of the polyvinyl acetal resin, the polyvinyl acetal resin undergoes phase change and precipitates under a low temperature environment, and epoxy cellulose is added after the precipitation is complete. At this time, in the presence of an acidic catalyst, the epoxy groups in the epoxy cellulose are protonated, the polarity of the CO bond increases, the bond energy decreases, and then breaks, thereby successfully grafted onto the side chain of the polyvinyl acetal resin. The polyvinyl acetal resin has thixotropy, the side chain length of the polyvinyl acetal resin molecule is increased, and after modification, it contains a large number of hydroxyl groups, which can enhance the adhesion between the polyvinyl acetal resin and the inorganic powder, and can also form a cross-linked network due to the interaction between themselves, thereby improving the anti-sedimentation performance.

[0039] Preferably, the mass ratio of the polyvinyl acetal resin A to the polyvinyl acetal resin B is (2-5):(5-8).

[0040] Preferably, the molecular weight of the polyvinyl acetal resin A is 25000-40000, the hydroxyl content is 25-40 mol%, and the acetalization degree is 60-75 mol%; the molecular weight of the polyvinyl acetal resin B is 45000-150000, the hydroxyl content is 20-35 mol%, and the acetalization degree is 65-80 mol%.

[0041] By adopting the above technical scheme, in order to obtain a slurry composition with excellent performance, the binder used in the present invention is a polyvinyl acetal resin composition, in addition to the polyvinyl acetal resin B, a part of low molecular weight polyvinyl acetal resin A is also added, the polyvinyl acetal resin B needs to be grafted with epoxy cellulose, has a high degree of polymerization, and has high mechanical strength, but the viscosity is too large, which is not conducive to resin dissolution and processing casting. Therefore, the polyvinyl acetal resin A is compounded, and the viscosity of the polyvinyl acetal resin B can be adjusted without affecting the compatibility between the slurry components, thereby obtaining a slurry composition with excellent processing performance, good mechanical strength and anti-settling performance.

[0042] In a second aspect, the present invention provides a method for preparing a slurry composition, comprising the following preparation steps:

[0043] S1. The polyvinyl acetal resin A and the polyvinyl acetal resin B are mixed in proportion to obtain a polyvinyl acetal resin composition; the polyvinyl acetal resin composition and the plasticizer are added to an organic solvent and stirred until completely dissolved to obtain a resin solution;

[0044] S2. Add inorganic powder to the resin solution, stir and mix, and then ball mill for 2 to 3 hours to obtain a slurry composition.

[0045] By adopting the above technical solution, the polyvinyl alcohol acetal resin composition is first dissolved in an organic solvent, which can effectively avoid the presence of micelles, thereby improving the adhesion between the substrate materials. The obtained slurry composition composite system has good uniformity and stability, which can greatly optimize the cracking phenomenon that may occur during high-temperature sintering in the subsequent processing process, thereby obtaining a finished product with excellent performance, and also greatly improving the production efficiency.

[0046] In a third aspect, the present invention provides an application of a slurry composition, wherein the slurry composition is applied to one of electronic ceramic green bodies, conductive pastes, ink printing, piezoelectric actuators, and solid oxide fuel cells.

[0047] More preferably, the slurry composition is applied to electronic ceramic green bodies.

[0048] Beneficial effects of the present invention:

[0049] 1. The slurry composition of the present invention contains polyvinyl acetal resin B, on the side chain of which epoxy cellulose is grafted, which can give the polyvinyl acetal resin a certain thixotropy, improve the flowability and dispersibility of the slurry composition, and form a cross-linked network structure between the molecular chains of the modified polyvinyl acetal resin, so as to better wrap the inorganic powder and achieve the purpose of preventing sedimentation, while uniformly dispersing the inorganic powder in the solvent.

[0050] 2. The polyvinyl acetal resin composition added to the slurry composition of the present invention is obtained by compounding polyvinyl acetal resin A and polyvinyl acetal resin B. The introduction of low molecular weight polyvinyl acetal resin A can better regulate the viscosity of the slurry composition, prevent excessive viscosity from causing the resin to be difficult to dissolve and subsequent processing difficulties, thereby obtaining a slurry composition with excellent processing performance, good mechanical strength and anti-settling performance. DETAILED DESCRIPTION

[0051] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Preparation Example

[0053] Preparation Example 1: A polyvinyl acetal resin B is prepared according to the following method:

[0054] Preparation of epoxy cellulose: 10 g of cellulose (particle size of 10 to 100 μm) was added to 250 mL of a 200 mmol / L sodium hydroxide aqueous solution, stirred and mixed at room temperature for 4 hours, and then dried to obtain pretreated cellulose; the pretreated cellulose, 180 g of epichlorohydrin and 14.5 g of sodium hydroxide were mixed, stirred and mixed for 30 minutes in a nitrogen atmosphere, 0.5 g of tetramethylammonium bromide was added, the temperature was increased to 65°C, the reaction was stirred for 6 hours, and finally the epoxy cellulose was obtained by filtering, washing, suction filtration and drying.

[0055] Preparation of polyvinyl alcohol acetal resin B: 100g of polyvinyl alcohol (alcoholysis degree 99.05mol%) with an average degree of polymerization of 1000 is added to 1150g of water, and the mixture is stirred and dissolved at 95°C to obtain a polyvinyl alcohol aqueous solution; the temperature of the polyvinyl alcohol aqueous solution is lowered to 30°C, 12g of n-butyraldehyde and 48g of a 31% hydrochloric acid aqueous solution are added, and the mixture is stirred and mixed for 30min, the temperature is further lowered to 10°C, 48g of n-butyraldehyde is added, and 1g of the epoxy cellulose obtained above is added after the phase change precipitation is complete, the temperature is raised to 45°C after keeping the temperature for 30min, and the mixture is stirred and reacted for 2h, and finally the polyvinyl alcohol acetal resin B is obtained after neutralization, centrifugation and drying.

[0056] Preparation Example 2, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that the amount of epoxy cellulose added is 0.1 g.

[0057] Preparation Example 3, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that the amount of epoxy cellulose added is 2 g.

[0058] Preparation Example 4, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that the amount of epoxy cellulose added is 5 g.

[0059] Preparation Example 4, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that, in the preparation process of epoxy cellulose, an equal amount of dodecyl epoxypropyl ammonium chloride is used to replace epichlorohydrin.

[0060] Preparation Example 5, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that, in the preparation process of epoxy cellulose, an equal amount of chlorinated epoxyeicosatrienoic acid is used to replace epichlorohydrin.

[0061] Preparation Example 6, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that the amount of epoxy cellulose added is 8 g.

[0062] Preparation Example 7, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that the amount of epoxy cellulose added is 1 g.

[0063] Preparation Example 8, a polyvinyl acetal resin B, which is different from Preparation Example 1 only in that the polyvinyl acetal resin B is prepared according to the following method:

[0064] 100 g of polyvinyl alcohol (alcoholysis degree 99.05 wt%) with an average degree of polymerization of 1000 was added to 1150 g of water, and the solution was dissolved by stirring at 95° C. to obtain a polyvinyl alcohol aqueous solution; the temperature of the polyvinyl alcohol aqueous solution was lowered to 30° C., 12 g of n-butyraldehyde, 1 g of epoxy cellulose and 48 g of a 31% hydrochloric acid aqueous solution were added, and the mixture was stirred for 30 min, the temperature was further lowered to 10° C., 48 g of n-butyraldehyde was added, and the temperature was increased to 45° C. after keeping the temperature for 30 min, and the reaction was stirred for 2 h. Finally, the polyvinyl alcohol acetal resin B was obtained after neutralization, centrifugation and drying.

[0065] Preparation Example 9, a polyvinyl acetal resin B, which is different from Preparation Example 1 only in that the polyvinyl acetal resin B is prepared according to the following method:

[0066] 100 g of polyvinyl alcohol (99.05 wt% alcoholysis degree) with an average degree of polymerization of 1000 was added to 1150 g of water, and the mixture was dissolved by stirring at 95° C. to obtain a polyvinyl alcohol aqueous solution; the temperature of the polyvinyl alcohol aqueous solution was lowered to 30° C., 12 g of n-butyraldehyde and 48 g of a 31% hydrochloric acid aqueous solution were added, and the mixture was stirred for 30 min, the temperature was further lowered to 10° C., 48 g of n-butyraldehyde was added, and the mixture was kept warm for 30 min, then the temperature was raised to 45° C., and the mixture was stirred for 2 h. Finally, the polyvinyl alcohol acetal resin B was obtained by neutralization, centrifugation and drying.

[0067] Preparation Example 10, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that, during the preparation of polyvinyl acetal resin B, an equal amount of polyvinyl alcohol with an average degree of polymerization of 500 is used to replace polyvinyl alcohol with a degree of polymerization of 1000.

[0068] Preparation Example 11, a polyvinyl acetal resin B, is different from Preparation Example 1 only in that, during the preparation of polyvinyl acetal resin B, an equal amount of polyvinyl alcohol with an average degree of polymerization of 3000 is used to replace polyvinyl alcohol with a degree of polymerization of 1000.

[0069] Example

[0070] Example 1, a slurry composition is prepared according to the following steps:

[0071] S1. Take 4g of polyvinyl acetal resin A and 6g of the polyvinyl acetal resin prepared in Preparation Example 1 B and mix to obtain a polyvinyl acetal resin composition; the obtained polyvinyl acetal resin composition and 4g of triethylene glycol diisooctanoate were added to 60g of an organic solvent and stirred until completely dissolved to obtain a resin solution;

[0072] The average molecular weight of the polyvinyl acetal resin A is 30,000, the hydroxyl content is 25-30 mol%, and the acetalization degree is 60-65 mol%;

[0073] The organic solvent is a mixed solution of toluene and ethanol in a mass ratio of 3:2.

[0074] S2. Add 100 g of barium titanate to the above resin solution, stir and mix, and then ball mill for 2 hours to obtain a slurry composition.

[0075] Embodiments 2 to 5 are slurry compositions, which differ from Embodiment 1 only in that the raw material ratio of the slurry composition is adjusted within a range, as shown in Table 1:

[0076] Table 1 Slurry composition formula table of Example 1 to Example 5

[0077]

[0078] The polyvinyl acetal resin B used is the polyvinyl acetal resin B prepared in Preparation Example 1.

[0079] Example 6 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 2.

[0080] Example 7, a slurry composition, is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 3.

[0081] Example 8 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 4.

[0082] Example 9 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 5.

[0083] Example 10 is a slurry composition, which is different from Example 1 only in that the barium titanate is replaced by an equal amount of ferrite.

[0084] Example 11, a slurry composition, is different from Example 1 only in that barium titanate is replaced by an equal amount of graphene.

[0085] Example 12, a slurry composition, is different from Example 1 only in that the added amount of polyvinyl acetal resin A is 7 g, and the added amount of polyvinyl acetal resin B prepared in Preparation Example 1 is 3 g.

[0086] Example 13, a slurry composition, is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 6.

[0087] Example 14 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 7.

[0088] Example 15 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 8.

[0089] Example 16 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin A with an average molecular weight of 30,000 is replaced by an equal amount of polyvinyl acetal resin with an average molecular weight of 45,000.

[0090] Example 17, a slurry composition, is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 10.

[0091] Example 18, a slurry composition, is different from Example 1 only in that an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 11 is used to replace the polyvinyl acetal resin B prepared in Preparation Example 1.

[0092] Comparative Example

[0093] Comparative Example 1 is a slurry composition, which is different from Example 1 only in that the polyvinyl acetal resin B prepared in Preparation Example 1 is replaced by an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 9.

[0094] Comparative Example 2 is a slurry composition, which is different from Example 1 only in that an equal amount of the polyvinyl acetal resin B prepared in Preparation Example 1 is used to replace the polyvinyl acetal resin composition.

[0095] Comparative Example 3 is a slurry composition, which is different from Example 1 only in that an equal amount of polyvinyl acetal resin A is used to replace the polyvinyl acetal resin composition.

[0096] Performance testing

[0097] 1. Anti-settling performance test: The slurry compositions obtained in the examples and comparative examples were placed in an environment of 25° C. and 50% humidity, and after one month, it was confirmed whether the slurry compositions were stratified.

[0098] 2. Viscosity stability test: The slurry compositions obtained in the examples and comparative examples were placed at 25° C. for 1 month, and the viscosity change rate (%) before and after the test was measured.

[0099] 3. Application evaluation:

[0100] (1) Sample preparation: The slurry composition obtained in the examples and comparative examples was cast on a release film using a coater and dried to prepare a 20 μm resin sheet;

[0101] (2) Performance evaluation: The obtained resin sheet was peeled off from the release film, and the state of the resin sheet was visually observed and evaluated using the following criteria:

[0102] ○: The film can be completely peeled off, and no cracks or damage are observed on the sheet.

[0103] △: Can be completely peeled off from the film, but the sheet is cracked or damaged;

[0104] ×: It cannot be peeled off from the film, and there are many cracks and damages after peeling.

[0105] The above test results are shown in Table 2:

[0106] Table 2 Performance test results

[0107]

[0108] According to Table 2, in combination with Example 1, Example 2 to Example 11, it can be seen that the overall changes of Example 2 to Example 11 are not large compared with Example 1, among which the viscosity changes of Example 2, Example 3 and Example 8 are relatively large. The reason is that in Example 2 and Example 3, more polyvinyl acetal resin composition is added to the former, and too much binder will affect the viscosity stability of the slurry, while less polyvinyl acetal resin composition is added to the latter, and the ability to adjust the slurry composition is reduced. In Example 8, more epoxy cellulose is added, which will result in the molecular weight of the obtained polyvinyl acetal resin B being too large compared with Example 1 and Example 3, which will increase the overall viscosity of the slurry, and the intermolecular mobility will also decrease, and the viscosity stability will decrease.

[0109] Combining Example 1, Example 12, Comparative Example 2 and Comparative Example 3, it can be seen that the overall performance of Comparative Example 2 and Comparative Example 3 changes significantly, and the anti-settling performance decreases significantly. The reason is that the amount of polyvinyl acetal resin B added in Example 12 is reduced, which will reduce the overall mechanical properties of the slurry composition on the one hand, resulting in cracking during application evaluation, and on the other hand, it will affect the formation of the cross-linked network structure in the slurry composition, resulting in a decrease in anti-settling performance. Only a single polyvinyl acetal resin is added in Comparative Example 2 and Comparative Example 3, and polyvinyl acetal resin A is not added in Comparative Example 2, which makes it difficult to adjust the viscosity of the system, and the uniformity and viscosity stability of the system decrease; only polyvinyl acetal resin A is added in Comparative Example 3, without the help of polyvinyl acetal resin B, resulting in a significant decrease in anti-settling performance.

[0110] Combining Example 1 and Example 13, it can be seen that the stability and processing performance of Example 13 are reduced. The reason is that the R1 group of the epoxy group in Example 13 is an alkyl chain with more than 15 carbons, which will affect the grafting process of epoxy cellulose and reduce the grafting rate. It will also cause the viscosity of the obtained polyvinyl alcohol acetal resin B to increase significantly, thereby significantly changing the viscosity stability.

[0111] Combining Example 1, Example 14 and Comparative Example 1, it can be seen that the viscosity change rate of Example 14 and Comparative Example 1 is obvious. The reason is that during the preparation process of the polyvinyl alcohol acetal resin B in Example 14, an excessive amount of epoxy cellulose is added. Similarly, the grafting modification of a large amount of epoxy cellulose will cause the molecular weight of the obtained polyvinyl alcohol acetal resin to increase greatly, and will also affect the movement between the molecular chains. As one of the components of the slurry composition, it will seriously affect its processing performance. In Comparative Example 1, there is no polyvinyl alcohol acetal resin that has not been modified with epoxy cellulose. The dispersibility of the slurry composition is significantly reduced, and a cross-linked network structure cannot be formed, and the anti-sedimentation performance is significantly reduced.

[0112] Combining Example 1 and Example 15, it can be seen that the overall stability of Example 15 is reduced. The reason is that in the preparation process of polyvinyl acetal resin B in Example 15, epoxy cellulose is added during the dissolution process, which will seriously affect the grafting rate and cause epoxy cellulose to participate in the main chain polymerization process of polyvinyl acetal resin, thereby changing the structure of polyvinyl acetal resin B and affecting its performance.

[0113] In combination with Example 1 and Example 16 to Example 18, it can be seen that the overall performance of the slurry compositions of Example 16 to Example 18 has declined. The reason is that the average molecular weight of the polyvinyl acetal resin A added in Example 16 is 45,000, and its degree of polymerization is greater than 600, which will cause the viscosity of the obtained composition to be relatively large, the dispersibility of the inorganic powder to be significantly reduced, and the viscosity stability and anti-settling performance to be reduced; the molecular weight of the polyvinyl acetal resin B in Example 17 is less than 45,000, and its degree of polymerization is less than 800, which will seriously affect the application of the slurry composition. It can also be seen from the results of the application evaluation that the obtained resin sheet has poor strength and is very easy to break, and a completed resin sheet cannot be obtained; the molecular weight of the polyvinyl acetal resin B in Example 18 is greater than 150,000, and its degree of polymerization is greater than 3,000, so the viscosity of the obtained slurry composition is too high. Even with the adjustment of the polyvinyl acetal resin A, the slurry fluidity is still significantly reduced, and it is difficult to form a film.

[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A slurry composition, characterized in that: The slurry composition comprises the following raw materials in parts by weight: 100 parts of inorganic powder; 1 to 20 parts of a polyvinyl acetal resin composition; 3-5 parts of plasticizer; 50-70 parts of organic solvent; The polyvinyl acetal resin composition comprises polyvinyl acetal resin A and polyvinyl acetal resin B; the molecular chain side chain of the polyvinyl acetal resin B is grafted with epoxy cellulose.

2. The slurry composition according to claim 1, characterized in that The epoxy cellulose contains one or two or more epoxy groups; the molecular structure of the epoxy group is as follows: The R1 is a C1-C15 alkyl chain; the R includes one of -H and -CH3.

3. The slurry composition according to claim 2, characterized in that The epoxy cellulose comprises the following structural units: Wherein X, Y, and Z are any one of -H, -CH3 and epoxy groups; and the structural unit contains at least one or more epoxy groups.

4. The slurry composition according to claim 1, characterized in that The polyvinyl acetal resin B is prepared according to the following method: Add polyvinyl alcohol to water, stir and dissolve at 90-95° C. to obtain a polyvinyl alcohol aqueous solution; reduce the temperature of the polyvinyl alcohol aqueous solution to 30-35° C., add part of n-butyraldehyde and an acid catalyst, stir and mix for 30-60 minutes, continue to reduce the temperature to 5-10° C., add the remaining n-butyraldehyde, add epoxy cellulose after phase change and precipitation are complete, keep warm for 20-30 minutes, then raise the temperature to 40-50° C., stir and react for 2-3 hours, and finally obtain polyvinyl alcohol acetal resin B through neutralization, centrifugation and drying.

5. The slurry composition according to claim 4, characterized in that The added amount of the epoxy cellulose is 0.1-5% of the mass of the polyvinyl alcohol.

6. The slurry composition according to claim 1, characterized in that: The mass ratio of the polyvinyl acetal resin A to the polyvinyl acetal resin B is (2-5):(5-8).

7. The slurry composition according to claim 6, characterized in that: The molecular weight of the polyvinyl acetal resin A is 25000-40000, the hydroxyl content is 25-40 mol%, and the acetalization degree is 60-75 mol%; the molecular weight of the polyvinyl acetal resin B is 45000-150000, the hydroxyl content is 20-35 mol%, and the acetalization degree is 65-80 mol%.

8. The slurry composition according to claim 1, characterized in that The inorganic powder includes one of barium titanate, ferrite, aluminum oxide, silicon nitride, zirconium oxide and graphene.

9. A method for preparing a slurry composition according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1. The polyvinyl acetal resin A and the polyvinyl acetal resin B are mixed in proportion to obtain a polyvinyl acetal resin composition; the polyvinyl acetal resin composition and the plasticizer are added to an organic solvent and stirred until completely dissolved to obtain a resin solution; S2. Add inorganic powder to the resin solution, stir and mix, and then ball mill for 2 to 3 hours to obtain a slurry composition.

10. A use of the slurry composition according to any one of claims 1 to 8, characterized in that: The slurry composition is applied to one of electronic ceramic green bodies, conductive pastes, ink printing, piezoelectric actuators, and solid oxide fuel cells.